RANCANG BANGUN SISTEM INFORMASI AKUNTABILITAS KINERJA INSTANSI PEMERINTAH BERBASIS E-GOVERNMENT - Nur - Hayati (Lambung Mangkurat University, 2022)
The Government Agency Performance Accountability System (SAKIP) is an integrated system of planning systems, budgeting systems and performance reporting systems, which is in line with the implementation of the financial accountability system at the Disdukcapil Kab. Pekalongan. In this case, every organization is required to record and report every use of state finances and their compliance with applicable regulations. The design of the E-SAKIP information system uses a Data Flow Diagram (DFD), Entity Diagram, and Context Diagram model. The transition from manual technology to the use of databases and systems that facilitate reporting to the secretariat of the Disdukcapil Kab. Pekalongan. The E-SAKIP system makes it easier for decision makers to monitor government management systems that focus on increasing accountability as well as improving results-oriented performance (outcomes).Keywords: E-SAKIP, Design, Information Systems, Data Flow Diagrams Sistem Akuntabilitas Kinerja Instansi Pemerintahan (SAKIP) merupakan sistem integrasi dari sistem perencanaan, sistem penganggaran dan sistem pelaporan kinerja, yang selaras dengan pelaksanaan sistem akuntabilitas keuangan pada Disdukcapil Kab. Pekalongan. Dalam hal ini, setiap organisasi diwajibkan mencatat dan melaporkan setiap penggunaan keuangan negara serta kesesuaiannya dengan ketentuan yang berlaku. Perancangan sistem informasi E-SAKIP menggunakan model Data Flow Diagram (DFD), Entity Diagram, Context Diagram. Peralihan dari teknologi manual ke penggunaan database dan sistem yang memudahkan pelaporan kepada bagian kesekretariatan Disdukcapil Kab. Pekalongan. Sistem E-SAKIP memudahkan pemangku keputusan untuk memantau sistem manajemen pemerintahan yang berfokus pada peningkatan akuntabilitas serta sekaligus peningkatan kinerja yang berorientasi pada hasil (outcome). Kata kunci: E-SAKIP, Perancangan, Sistem Informasi, Data Flow Diagram